The Sustainability Liability: Potential Negative Effects of Ethicality on Product Preference - Luchs, Michael G.; Naylor, Rebecca Walker; Irwin, Julie R.; Raghunathan, Rajagopal (Journal of Marketing, 2010)
Manufacturers are increasingly producing and promoting sustainable products (i.e., products that have a positive social and/or environmental impact). However, relatively little is known about how product sustainability affects consumers’ preferences. The authors propose that sustainability may not always be an asset, even if most consumers care about social and environmental issues. The degree to which sustainability enhances preference depends on the type of benefit consumers most value for the product category in question. In this research, the authors demonstrate that consumers associate higher product ethicality with gentleness-related attributes and lower product ethicality with strength-related attributes. As a consequence of these associations, the positive effect of product sustainability on consumer preferences is reduced when strength-related attributes are valued, sometimes even resulting in preferences for less sustainable product alternatives (i.e., the “sustainability liability”). Conversely, when gentleness-related attributes are valued, sustainability enhances preference. In addition, the authors show that the potential negative impact of sustainability on product preferences can be attenuated using explicit cues about product strength.